Development from alloys to nanocomposite for an enhanced mechanical and ignition response in magnesium - Tun, Khin Sandar (2022)
The current study reports on the evolution of microstructure, variations in compressive properties and the ignition resistance of Mg through compositional variation, using alloying elements and nanoreinforcement. The alloys were designed with the use of a singular alloying element, Ca, and a binary alloying element, Ca+Sc, to develop Mg1Ca (wt.%) and Mg1Ca1Sc (wt.%) al-loys. B4 C nanoparticles were addedas the reinforcement phase in the Mg1Ca1Sc alloy to create the Mg1Ca1Sc/1.5B4 C (wt.%) nanocomposite. The most effective compressive properties and level of ignition resistance was displayed by the developed composite. The grain sizes were significantly reduced in the Mg alloys (81%) and the composite (92%), compared with that of the Mg. Overall, the microstructural features (i.e., grain refinement, the formation of favorable intermetallic com-pounds, and hard reinforcement particles with an adequate distribution pattern) enhanced both the compressive strength and strain of the alloys and the composite. The ignition resistance was progressively increased from the alloys to the nanocomposite, and a peak ignition temperature of 752◦ C was achieved in the composite. When compared with the ignition resistant of Elektron 21 (E21) alloy, which met the Federal Aviation Administration (FAA) requirements, the Mg1Ca1Sc/1.5B4 C nanocomposite showed a higher specific yield strength and better ignition resistance, asserting it as a potential candidate material for lightweight engineering applications, including aerospace and defense sectors.